2020
DOI: 10.1186/s13244-019-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions of UK medical students towards artificial intelligence and radiology: a multicentre survey

Abstract: Objectives: To explore the attitudes of United Kingdom (UK) medical students regarding artificial intelligence (AI), their understanding, and career intention towards radiology. We also examine the state of education relating to AI amongst this cohort. Methods: UK medical students were invited to complete an anonymous electronic survey consisting of Likert and dichotomous questions. Results: Four hundred eighty-four responses were received from 19 UK medical schools. Eighty-eight percent of students believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
273
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(315 citation statements)
references
References 12 publications
34
273
2
6
Order By: Relevance
“… 14 In Sit et al study, about half of their students obtained AI-related education, and students who did not obtain such education were significantly less likely to consider radiology as a career. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 In Sit et al study, about half of their students obtained AI-related education, and students who did not obtain such education were significantly less likely to consider radiology as a career. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 9,14–18 Misunderstanding about the effect of AI on radiology may discourage medical students from considering radiology as a specialty. 14 Previous studies in the same subject from Canada, 14 Germany, 19 UK 20 , and Brazil 21 concluded that AI played a negative role in medical students’ choice for radiology.…”
Section: Introductionmentioning
confidence: 99%
“…La expansión de la IA en la práctica médica ha generado debates sobre su aplicación en el área de la educación médica en las universidades. En el Reino Unido (UK), el uso de nuevos métodos digitales en salud ha sido objeto de un reciente gobierno nacional 30 . Topol explica con mucho énfasis explícito la importancia de las herramientas digitales novedosas en la enseñanza de pregrado y posgrado con el objetivo de ayudar a las futuras generaciones de estudiantes de medicina en su actividad clínica, incluidos los apoyados por la IA.…”
Section: Inteligencia Artificial En Estudiantes De Medicinaunclassified
“…Recently a number of surveys have explored medical students', and physicians' views about the impact of AI/ML on the future of medical practice [10][11][12][13][14][15][16]. Currently, there is scarce exploration of consensus views among informaticians [17]; in particular, on how AI/ML might meaningfully influence medical care in the short-term [18].…”
Section: Objectivesmentioning
confidence: 99%